Evaluation of Kerosene Fuelled Scramjet Combustor using a Combination of Cooled and Uncooled Struts - Chandrasekhar, C.; Ramanujachari, V.; Reddy, T. Kishen Kumar (Defence Science Journal, 2014)
The scramjet combustor a vital component of scramjet engine has been designed by employing fuel injection struts. Several experimental studies have been carried out to evaluate the propulsive performance and structural integrity of the in-stream fuel injection struts in the connect-pipe test facility. As the mission objective of hypersonic demonstrator is to flight test the scramjet engine for 20 s duration, in-stream fuel injection struts which are designed as heat sink devices encounter hostile flow field conditions especially in terms of high thermal and high convective loads in the scramjet combustor. To circumvent these adverse conditions, materials like Niobium C-103 and W-Ni-Fe alloys have been used for the construction of struts and a number of tests have been carried out to evaluate the survivability of the in-stream fuel injection struts in the scramjet combustor. The results thus obtained show that the erosion of leading edges of the Stage-II fuel injection struts in the initial phase and subsequently puncturing of the fuel injection manifold after 10-12 s of the test are noticed, while the other stages of the struts are found to be intact. This deteriorating leading edges of Stage-II struts with respect to time, affect the overall propulsive performance of the combustor. To mitigate this situation, Stage-II struts have been designed as cooled structure and other Stages of struts are designed as un-cooled structure. Material of construction of struts used is Nimonic C-263 alloy. This paper highlights the results of the static test of the scramjet combustor, which has been carried out at a combustor entry Mach number of 2.0, total temperature of 2000 K, with an overall kerosene fuel equivalence ratio of 1.0 and for the supersonic combustion duration of 20 s. Low back pressure has been created at the exit of the scramjet combustor using ejector system to avoid flow separation.Visual inspection of the fuel injection struts after the test revealed that all the Struts are found to be thermo-structurally safe in the combustor environment except for minor erosion of the leading edges of the struts. Stage-II struts made of two-passage cooled configuration are found to be thermo-structurally safe. Although other stages of struts used in the test are of un-cooled configuration, they too are found to be safe and intact. This demonstrates the fact that they experience thermally benign flow conditions compared to Stage-II struts in the scramjet combustor. Defence Science Journal, 2014, 64(1), DOI:http://dx.doi.org/10.14429/dsj.64.2733